2022-RA-708-ESGO Real-world assessment of patients with ovarian cancer who received niraparib as second-line maintenance therapy in the United States: did first-line maintenance approval change the patient profile for second-line maintenance therapy?. (20th October 2022) - Backes, Floor; Calderón Boyle, Tirza Areli; Perhanidis, Jessica; Lim, Jonathan; Kalilani, Linda; Hurteau, Jean A; Golembesky, Amanda; Salani, Ritu
Abstract : Introduction/Background: Niraparib, a poly(ADP-ribose) polymerase inhibitor (PARPi), was first approved in the US on 27 Mar 2017 for maintenance treatment of recurrent epithelial ovarian cancer (EOC). To evaluate whether approval of niraparib first-line maintenance (1LM) affected the clinical profile of patients receiving niraparib second-line maintenance (2LM), this study described the characteristics of real-world patients with EOC who initiated 2LM with niraparib before and after niraparib 1LM approval, using a real-world database. Methodology: This retrospective cohort study from the nationwide electronic health record-derived de-identified Flatiron Health database and included patients who were diagnosed with EOC between 01Jan2011 and 30Nov2021, were ≥18 years old at diagnosis, and received 1L platinum-based therapy. The index date was defined as the initiation date of niraparib 2LM monotherapy, on or after 01Jan2017. Demographic and clinical characteristics were assessed from EOC diagnosis to index date. Patients were stratified by index date: before 29Apr2020 (niraparib 1LM preapproval cohort) and after 29Apr2020 (niraparib 1LM postapproval cohort). Results: 231 2LM niraparib monotherapy patients were included, with all receiving 2L platinum-based therapy. The median age was 68 years, and patients were primarily treated in a community setting (90.0%; table 1 ). The majority of patients had stage III/IV disease at diagnosis (78.4%) and had BRCA wild-type ( BRCA wt, 74.0%). Homologous recombination deficiency status was unknown for most patients (92.2%). Median time from initial EOC diagnosis to 2L maintenance therapy was 803 days. Patient characteristics were broadly similar across the stratified cohorts, with a higher proportion of patients with BRCA wt in the niraparib 1LM postapproval cohort than in the preapproval cohort (85.3% vs 68.6%). Conclusion: This real-world analysis found that niraparib remained an important treatment option for 2LM in patients with recurrent EOC following niraparib 1LM approval, and that 1LM approval did not markedly change the profile of patients receiving niraparib maintenance therapy in a 2L setting.